2019
DOI: 10.1177/2192568219853222
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Use Affects Pseudarthrosis Rates and Influences Patient-Reported Outcomes

Abstract: Study Design: Retrospective cohort review Objectives: Cervical pseudarthrosis is a frequent cause of need for revision anterior cervical discectomy and fusion (ACDF) and may lead to worse patient-reported outcomes. The effect of proton pump inhibitors on cervical fusion rates are unknown. The purpose of this study was to determine if patients taking PPIs have higher rates of nonunion after ACDF. Methods: A retrospective cohort review was performed to compare patients who were taking PPIs preoperatively with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Interestingly, non-unions never reached consensus as a post-operative complication. This outcome is particularly challenging to assess, as it has been frequently identified during long-term follow-up, and has been associated with numerous non-surgical patient factors, such as medication use, smoking, and systemic comorbidities [ 47 , 48 ]. As such, it is difficult to ascertain the role that operative factors may play in contributing to pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, non-unions never reached consensus as a post-operative complication. This outcome is particularly challenging to assess, as it has been frequently identified during long-term follow-up, and has been associated with numerous non-surgical patient factors, such as medication use, smoking, and systemic comorbidities [ 47 , 48 ]. As such, it is difficult to ascertain the role that operative factors may play in contributing to pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although we acknowledge that this result needs to be confirmed on a larger sample, previous studies showed that patients taking PPIs have an increased the risk of non-union in tibial and femoral shaft fractures compared with non-users [ 32 ]. Another recent report has shown that patients on PPIs may have higher non-union rates following an anterior cervical discectomy and fusion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential link between nonunion and JK/JF should lead the surgeon to ensure that fusion is indeed established, either by optimizing the surgical strategy or by eliminating risk factors such as postoperative nonsteroidal anti-inflammatory drugs,[ 22 ] steroids,[ 23 ] or proton-pump inhibitors. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%